Evaluation of curing process-induced deformation in plain woven composite structures based on cure kinetics considering various fabric parameters. (1st May 2022) - Kim, Dong-Hyeop; Kim, Sang-Woo; Lee, In
Abstract: This study evaluates the curing process-induced deformation of the plain woven composite structures based on calculation of effective material property, by considering fabric parameters closely related to the material properties. The theoretical models for predicting the cure behavior and effective material property of the thermosetting woven composites were coded and incorporated into finite element-based three-dimensional cure simulation to investigate in detail the deformation according to the curing stage. The results revealed that the deformation of the fully cured woven composite structure increased with an increase in the composite yarn thickness; however, the deformation decreased when the thickness of the woven composite lamina was greater than 0.9 mm. Furthermore, the deformation due to the curing process increased with an increase in the gap between adjacent yarns. The process-induced deformation considering the fabric parameters evaluated in this study can contribute to improving the manufacturing quality of woven composite structures during their development phase.